High frequency stimulation of the subthalamic nucleus modulates neuronal activity in the lateral habenula nucleus - Hartung, H; Tan, S; Temel, Y; Sharp, T (John Wiley & Sons Ltd, 2016)
High frequency stimulation (HFS) of the subthalamic nucleus (STN) is often used to treat movement disability in advanced Parkinson's disease, but some patients experience debilitating psychiatric effects including depression. Interestingly, HFS of the STN modulates 5-HT neurons in the dorsal raphe nucleus (DRN) which are linked to depression, but the neural substrate of this effect is unknown. Here we tested the effect of STN stimulation on neuronal activity in the lateral habenula nucleus (LHb), an important source of input to DRN 5-HT neurons and also a key controller of emotive behaviours. LHb neurons were monitored in anaesthetised rats using single unit extracellular recording, and localisation within the LHb was confirmed by juxtacellular labelling. HFS of the STN (130 Hz) evoked rapid changes in the firing rate of the majority of LHb neurons tested (38 of 68). Some LHb neurons (19/68) were activated by HFS while others (19/68), distinguished by a higher basal firing rate, were inhibited. LHb neurons that project to the DRN were identified using antidromic activation and collision testing (n=17 neurons). Some of these neurons (5/17) were also excited by HFS of the STN, and others (7/17) were inhibited although this was only a statistical trend. In summary, HFS of the STN modulated the firing of LHb neurons, including those projecting to the DRN. The data identify that the STN impacts on the LHb-DRN pathway. Moreover, this pathway may be part of the circuitry mediating the psychiatric effects of STN stimulation experienced by patients with Parkinson's disease. This article is protected by copyright. All rights reserved.